2008
DOI: 10.1182/blood-2007-08-107664
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the α2β1 integrin and c-met/HGF-R regulates innate immunity

Abstract: Data from several investigators suggest that the ␣2␤1 integrin, a receptor for collagens, laminins, decorin, E-cadherin, matrix metalloproteinase-1, endorepellin, and several viruses, is required for innate immunity and regulation of autoimmune/ allergic disorders. We demonstrated that the innate immune response to Listeria monocytogenes required ␣2␤1 integrin expression by peritoneal mast cells (PMCs). Ligation of the ␣2␤1 integrin by C1q contained in immune complexes comprised of Listeria and antibody was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 67 publications
1
40
0
Order By: Relevance
“…The signaling properties of integrin receptors are dictated primarily by their state of activation resulting from ECM ligand occupancy and/or cis-transactivation through interaction with 3367 RESEARCH ARTICLE Integrins in islet development growth factor receptors harboring tyrosine kinase functions, rather than by their levels of expression (Fujita et al, 2013;Giancotti and Ruoslahti, 1999;Ju and Zhou, 2013;Liddington and Ginsberg, 2002;Margadant et al, 2011;McCall-Culbreath et al, 2008;Mitra et al, 2011;Wang et al, 1998). Nevertheless, it is reasonable to infer that the levels of β1 integrin expression detected in different pancreatic epithelial cell types correlate with cell type-specific proliferative capabilities.…”
Section: Discussionmentioning
confidence: 94%
“…The signaling properties of integrin receptors are dictated primarily by their state of activation resulting from ECM ligand occupancy and/or cis-transactivation through interaction with 3367 RESEARCH ARTICLE Integrins in islet development growth factor receptors harboring tyrosine kinase functions, rather than by their levels of expression (Fujita et al, 2013;Giancotti and Ruoslahti, 1999;Ju and Zhou, 2013;Liddington and Ginsberg, 2002;Margadant et al, 2011;McCall-Culbreath et al, 2008;Mitra et al, 2011;Wang et al, 1998). Nevertheless, it is reasonable to infer that the levels of β1 integrin expression detected in different pancreatic epithelial cell types correlate with cell type-specific proliferative capabilities.…”
Section: Discussionmentioning
confidence: 94%
“…Similar results were obtained by Feng and colleagues (46), who showed that EC adhesion and spreading on C1q-coated microtiter wells was prevented both by mAb 60.11 to gC1qR and mAb to b 1 integrins and that gC1qR and b 1 integrin cocaptured on C1q-bound ECs. Involvement of integrins in cell activation by C1q has also been established on murine mast cells that have been shown to express a 2 b 1 integrin as a novel receptor for the collagen-like sequence of C1q (64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in mice gene targeting of the MET signaling pathway, through deletion of the gene encoding plasminogen activator, urokinase receptor (Plaur), which controls levels of HGF, results in reduced numbers of neocortical interneurons, spontaneous seizures (which occur in 20%-30% of children with ASD), increased anxiety, and reduced social interactions (76)(77)(78). Additionally, MET signaling participates in autonomic nervous system and cerebellar development, immune function, and gastrointestinal function and repair (79)(80)(81)(82)(83)(84). Disruptions of these neural and peripheral elements have been reported in ASD (85)(86)(87)(88)(89)(90).…”
Section: The Basics Of Cnvsmentioning
confidence: 99%